A retrospective review of UVA1 treatment: An Australian experience from a single centre. (10th May 2020) - Pitney, Thomas; Pitney, Michael J
Abstract: Background: The therapeutic value of ultraviolet A1 (UVA1) phototherapy has been acknowledged for many years. Initially developed predominately for experimental and diagnostic purposes, it was subsequently recognised as a beneficial therapeutic modality in atopic dermatitis and localised scleroderma, and more recently a variety of sclerosing and fibrosing dermatoses, T‐lymphocyte mediated disorders, both inflammatory and infiltrative, and several predominately dermal processes previously unresponsive to current therapies. Methods: We present a retrospective evaluation of outcomes and treatment tolerability in adult patients using a low dose (30 joules/cm 2 ), regimen administered in our private dermatologic practice, between 2006 and December 2019. Results: Major clinical groups represented include atopic dermatitis, localised and systemic sclerodermas, mycosis fungoides, urticarial dermatitis, generalised pruritus and granuloma annulare. Eighty‐seven patients are included in this study with 92% of all patients experiencing a beneficial result, 54% having complete and 38% partial relief of presenting signs and/or symptoms. UVA1 therapy was well tolerated, with no patients ceasing treatment due to adverse effects. Conclusions: Ultraviolet A1 is an effective and safe treatment option in many hitherto recalcitrant cutaneous conditions.